Melindrosas e almofadinhas: gender figurations in Recife in the 1920's (Tempo e Argumento, 2010)
The aim of this paper is to analyze the configuration of the gender relations in Recife, during the 1920s, athwart two stereotype-characters that appeared in the press discourses: the melindrosa and the almofadinha. These characters exemplify an opening in the behaviors standardized in the gender relations, what exposed them to critics and jokes. This work analyzes two newspapers of different typologies (the Jornal do Commercio and the magazine a Pilhéria) throughout Elias’ figurational sociology, discourse analysis and the theories about gender relations. Hence, this work aims at contributing to the discussions about gender, adding new historical elements that can help to review daily prejudices.
Keywords: gender; press; discourse